ANALYSIS OF TAXATION MECHANISMS FOR AGRICULTURAL ENTERPRISES IN THE REGIONS (Archive of Conferences, 2020)
The article analyzes the mechanisms of taxation of agricultural enterprises engaged in agricultural activities in the regions on the example of Surkhandarya region.